From therapeutics to prophylaxis: the case for road safety audits internationally - Ramos, M. (Uluslararasi Trafik Magdurlari Konferansi - Trafif Magdurlarinin Yasaminda "Adalet" in Onemi - 13 Sept. IStabul, Bilgi Universitesi Sntral Kampusu, 2013)
in public health terms, road danger reduction means that we should take therapeutic action as having prophilatic effects, namely because it sensitizes societies to the need of improving social perception of road risk. This implies that victims' rights, and their active participation in post-crash investigation procedures, are a benefit for the proper improvement of road systems.